A hybrid approach of fuzzy risk assessment-based incenter of centroid and MCDM methods for multimodal transportation route selection. Issue 1 (31st December 2022) - Koohathongsumrit, Nitidetch; Chankham, Wasana
Abstract: Owing to its relevance to several conflicting decision criteria, subjective information, different preferences, and ambiguities, multimodal transportation route selection is a multiple-criteria decision-making problem. The main research question involved here is whether decision-makers require a tool to select multimodal freight routes based on quantitative and qualitative decision criteria, including decision-makers' preferences. This study proposes a novel hybrid approach that integrates fuzzy risk assessment-based incenter of centroid method, fuzzy analytic hierarchy process (AHP), and VIKOR (Vlse Kriterijumska Optimizacija I Kompromisno Resenje). The incenter of centroid method of fuzzy risk assessment produces precise results of risk levels, while the extent analysis on fuzzy AHP computes relative weights of attributes. Transportation cost and time, reliable risk magnitudes, and priority values are synthesized using VIKOR. The effectiveness and applicability of the proposed approach were verified through an empirical route selection from Thailand to China. The proposed methodology appropriately answers the research question by providing the most optimal transportation route and systematically yields the best compromise solution among all decision-making elements. The contributions of this study provide a new decision support model and aid decision-makers in designing comprehensive transportation planning under uncertainties.